CP-012 Structured pharmacist review of medication in older hospitalised patients: a cost effectiveness analysis. (25th February 2017) - Gallagher, J; O'Sullivan, D; McCarthy, S; Gillespie, P; Woods, N; O'Mahony, D; Byrne, S
Abstract : Background: A recent cluster randomised controlled trial (RCT) conducted in a major tertiary referral hospital evaluating a structured pharmacist review of medication (SPRM), supported by computerised clinical decision support software (CDSS), demonstrated positive outcomes in terms of reduction of adverse drug reactions (ADRs). Purpose: The purpose of this study was to examine the cost effectiveness of pharmacists applying an SPRM in conjunction with CDSS to older hospitalised patients compared with usual pharmaceutical care. Material and methods: Cost effectiveness analysis alongside a cluster RCT was performed. The trial was conducted in a tertiary hospital in the south of Ireland. Patients in the intervention arm (n=361) received a multifactorial intervention consisting of medicines reconciliation, deployment of CDSS and generation of a pharmaceutical care plan. Patients in the control arm (n=376) received usual care from the hospital pharmacy team. Incremental cost effectiveness was examined in terms of costs to the healthcare system and an outcome measure of ADRs during an inpatient hospital stay. Uncertainty in the analysis was explored using a cost effectiveness acceptability curve. Results: On average, the intervention arm was the dominant strategy in terms of cost effectiveness. Compared with usual care (control), the intervention was associated with a decrease of €807 (95% CI −3443 to 1829; p=0.548) in mean healthcare cost and a decrease in the mean number of ADR events per patient of −0.064 (95% CI −0.135 to 0.008; p=0.081). The probability of the intervention being cost effective at respective threshold values of €0, €250, €500, €750, €1000 and €5000 was 0.707, 0.713, 0.716, 0.718, 0.722 and 0.784, respectively. Conclusion: Based on the evidence presented, SPRM/CDSS is likely to be determined to be cost effective compared with usual pharmaceutical care. However, neither incremental costs nor effects demonstrated a statistically significant difference, and therefore the results of this single site study should be interpreted with caution. No conflict of interest